2017
DOI: 10.1037/rel0000098
|View full text |Cite
|
Sign up to set email alerts
|

The meaning as a buffer hypothesis: Spiritual meaning attenuates the effect of disaster-related resource loss on posttraumatic stress.

Abstract: Religious and spiritual beliefs serve a number of functions, including promoting mental health in the wake of negative life events. We explore the "meaning as a buffer" hypothesis, which posits that (spiritual) meaning will shield individuals from the negative psychological consequences associated with adversity. Building on Park's (2010) meaning making model, we investigated whether spiritual meaning can buffer the effect of disaster-related resource loss on posttraumatic stress. Survivors of Hurricane Katrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 43 publications
(59 reference statements)
7
31
0
Order By: Relevance
“…The finding that MIL moderates the association between goal violations and PTS symptoms is in line with previous studies demonstrating a buffering effect of MIL on negative mental health outcomes (e.g., Haynes et al, 2017;Marco et al, 2017). We extended those findings by showing that MIL might exert those effects by buffering the violations that are often associated with the experience of stressful life events.…”
Section: Moderating Effect Of Experienced Milsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding that MIL moderates the association between goal violations and PTS symptoms is in line with previous studies demonstrating a buffering effect of MIL on negative mental health outcomes (e.g., Haynes et al, 2017;Marco et al, 2017). We extended those findings by showing that MIL might exert those effects by buffering the violations that are often associated with the experience of stressful life events.…”
Section: Moderating Effect Of Experienced Milsupporting
confidence: 90%
“…A higher sense of MIL has not only been related to better mental health outcomes in a variety of populations (Blackburn & Owens, 2015;Brassai, Piko, & Steger, 2011;Steger & Kashdan, 2013;Winger, Adams, & Mosher, 2016) but also has been shown to moderate the relationship between stressful life events and negative outcomes (Cohen & Cairns, 2012;Halama & Bakosova, 2009;Haynes et al, 2017;Krause, 2007;Marco, Guillén, & Botella, 2017;Mascaro & Rosen, 2006;Szymanski & Mikorski, 2016). A recent study additionally demonstrated a buffering effect of MIL on the relationship between sacred loss (i.e., the perceived loss of the sacred character of parts of one's life) and indicators of physical health (Krause, Pargament, & Ironson, 2018).…”
mentioning
confidence: 99%
“…But more than this, Frankl saw meaning as being one of the most important resources for coping with adversity: "There is nothing in the world, I would venture to say, that would so effectively help one to survive even the worst conditions as the knowledge that there is a meaning in one's life" ([1946] 1984:126). Consistent with the views of Frankl ([1946] 1984), findings from a number of studies suggest that a sense of meaning in life moderates the effects of stress on health (e.g., Haynes et al 2015;Krause 2007;Krause, Pargament, and Ironson 2017;Krok 2016).…”
Section: Meaning In Life As a Coping Resourcesupporting
confidence: 66%
“…Consistent with the views of Frankl ([] 1984), findings from a number of studies suggest that a sense of meaning in life moderates the effects of stress on health (e.g., Haynes et al. ; Krause ; Krause, Pargament, and Ironson ; Krok ).…”
Section: Introductionsupporting
confidence: 54%
“…Negative religious appraisals of an event (i.e., the notion of being punished by God) was associated with the severity of symptoms of mental disorders in Berzengi et al (), Blanc, Rahill, Laconi, and Mouchenik (), Feder et al (), Sezgin & Punamäki, (, although the “human” appraisals were associated with even more severe psychopathology), and Rosellini et al (). Meaning‐making appraisals, on the contrary, were associated with resilience (de la Rosa, Barnett‐Queen, Messick, & Gurrola, ) and lower severity of PTSD symptoms (Haynes et al, ). Some studies examined the associations between general religiosity and religious coping; however, most studies that measure religious coping did not assess general religiosity.…”
Section: Resultsmentioning
confidence: 99%